The Relationship Between Response Inhibition Deficits and Intimate Partner Violence Perpetration - (:unkn) unknown (My University, 2022)
Victims of intimate partner violence (IPV) perpetration suffer from lasting deleterious impacts of trauma. Although various risk factors of IPV have been explored, fewer studies have focused on executive functioning as potential risk factors for IPV perpetration. Response inhibition is a form of cognitive control which serves to stop the initiation of a maladaptive action/response. Within the context of IPV, adaptive response inhibition may inhibit utilizing aggression as a conflict strategy. Therefore, exploring the relationship between response inhibition deficits and IPV may further our understanding of IPV perpetration. This study sought to explore the relationship between response inhibition and IPV in young LGB+ adults (N=207) while controlling for related IPV covariates. More specifically, how deficits in response inhibition correlate to specific types of IPV and if response inhibition deficits predict future IPV perpetration. The results showed that response inhibition was not significantly related to IPV perpetration, however, future research is needed to further explore how response inhibition may affect other aspects of IPV perpetration. Keywords: Intimate Partner Violence; Response Inhibition; Stop Signal Task